Fibrosing colonopathy in an adult owing to over use of pancreatic enzyme supplements. Issue 2 (1st February 2000) - Bansi, D S; Price, A; Russell, C; Sarner, M
Abstract : A woman, then in her late 20s, underwent a cholecystectomy in 1962 for gallstone disease and subsequent common bile duct stones were managed endoscopically. However, because of unrelenting pain, a pylorus preserving pancreaticoduodenectomy was done in 1990 and in the following years the patient took large amounts of pancreatic enzyme supplements. She developed large bowel obstruction in 1997 and a right hemicolectomy was undertaken. Histology confirmed fibrosing colonopathy of the ascending colon and caecum. Her pancreatic enzyme dose was reduced and her subsequent course has been uncomplicated.